State-space estimation of multi-factor models of the term structure : application to Government of Jamaica bonds - Langrin, R. Brian ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 2006)
Estimates two famous equilibrium models of the term structure of interest rates using zero-coupon Government of Jamaica sovereign bonds for the period 24 September 2004 to 28 July 2006. Seeks to explain the yield curve dynamics in Jamaica in order to derive information on investor expectation to support monetary and fiscal policy objectives as well as to accurately price bonds and hedging instruments.